Studi Cemaran Logam Berat (Fe, Pb, Cd, Cu dan Zn) dalam Umbi Singkong di Sekitar Area Eks Tempat Pemrosesan Akhir Leuwi Gajah - Febrianto, Arry; Buchari (Journal Serambi Engineering, 2024)
Heavy metals analysis on cassava around Ex Leuwi Gajah Landfill aimed to determine the effects of waste and leachate that contain heavy metals on plants nearby. The analysis was conducted from soil and cassava root samples. The determined heavy metals compounds are Fe, Pb, Cd, Cu, and Zn. Sample destruction was conducted by ash method and then analyzed by Atomic Absorption Spectrophotometry with curve calibration method. We also analyzed the sample's water, ash, and silica content from the gravimetric method. The analysis results were compared with the control variable by the student t-test method. There is no Cd detected on all cassava samples analysis. On the other hand, Pb concentration detected exceeded the Indonesia National Standard (SNI) and Food and Agriculture Organization / World Health Organization (FAO/WHO) permissible limits about heavy metal compounds on food and plants. The student t-test result shows a significant difference in heavy metals content between cassava in landfill and cassava control variables.